2018
DOI: 10.1021/acs.energyfuels.8b02665
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a High-Performance Biosorbent for Natural Gas Dehydration

Abstract: Dehydration of gases is crucial in industry. Current dehydration methods have concerns about high energy consumption and environmental pollution. In this work, natural gas, an important energy source, was selected as a model gas to investigate dehydration using a cost-effective biosorbent in a pressure swing adsorption process. The biosorbent was developed from flax shives, a byproduct of the flax industry, and are representative of renewable cellulose materials. The morphology, surface functional groups, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 45 publications
3
14
0
Order By: Relevance
“…A value of 10.32 J/mol was obtained for the CO 2 interaction forces, which shows attraction among the molecules. Ghanbari et al reported values of 6.4 and 8.33 J/mol at 35 and 50 °C, respectively, for the interaction forces among water molecules adsorbed on the surface of a flax-shive-based biosorbent . These forces are much weaker than van der Waals weak forces (400–4000 J/mol) and hydrogen bonds, such as HO–H···OH 3 + (18 000 J/mol) .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A value of 10.32 J/mol was obtained for the CO 2 interaction forces, which shows attraction among the molecules. Ghanbari et al reported values of 6.4 and 8.33 J/mol at 35 and 50 °C, respectively, for the interaction forces among water molecules adsorbed on the surface of a flax-shive-based biosorbent . These forces are much weaker than van der Waals weak forces (400–4000 J/mol) and hydrogen bonds, such as HO–H···OH 3 + (18 000 J/mol) .…”
Section: Resultsmentioning
confidence: 99%
“…Because only CO 2 was adsorbed by the adsorbent (helium carrier gas), we remove the subscript i from the rate of adsorption term (this term is assumed to be 0 for the carrier gas). The LDF is one of the most common expressions used for the rate of adsorption term in the equation, which takes the following form: where q * is the biosorbent loading at equilibrium with the gas phase and k LDF is the effective mass transfer coefficient (s –1 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations